The effect of live streaming and customer reviews on purchase decisions with brand trust as a mediating variable in TikTok Shop - Sari, Yunita; Indriastuti, Herning (Priviet Social Sciences Journal, 2026)
The Influence of Live Streaming and Customer Reviews on Purchase Decisions, and the Role of Brand Trust as an Intervening Variable on Products in TikTok Shop. Supervised by Dr. Herning Indriastuti, SE., MM. This study investigates the effect of live streaming and customer reviews on purchase decisions while examining brand trust as an intervening variable in the context of products marketed through TikTok Shop. Employing a quantitative approach with Partial Least Squares (PLS) analysis, the research involved 133 active TikTok Shop users who had watched live streaming sessions, read customer reviews, and made purchases. The findings reveal that live streaming and customer reviews positively and significantly influence both brand trust and purchase decisions. Furthermore, brand trust significantly affects purchase decisions and serves as a mediating variable in the relationship between live streaming, customer reviews, and purchase decisions, thereby underscoring the critical role of brand trust in optimizing the effectiveness of digital marketing strategies on TikTok Shop.